2016
DOI: 10.1111/1365-2656.12563
|View full text |Cite
|
Sign up to set email alerts
|

The dominant detritus‐feeding invertebrate in Arctic peat soils derives its essential amino acids from gut symbionts

Abstract: Supplementation of nutrients by symbionts enables consumers to thrive on resources that might otherwise be insufficient to meet nutritional demands. Such nutritional subsidies by intracellular symbionts have been well studied; however, supplementation of de novo synthesized nutrients to hosts by extracellular gut symbionts is poorly documented, especially for generalists with relatively undifferentiated intestinal tracts. Although gut symbionts facilitate degradation of resources that would otherwise remain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…, Larsen et al. ) in that the studied consumers were depleted rather than enriched relative to food resources. Symbiotic supplementation usually leads to enriched 13 C values in hosts because of respiration of isotopically light CO 2 (McConnaughey et al.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…, Larsen et al. ) in that the studied consumers were depleted rather than enriched relative to food resources. Symbiotic supplementation usually leads to enriched 13 C values in hosts because of respiration of isotopically light CO 2 (McConnaughey et al.…”
Section: Discussionmentioning
confidence: 97%
“…, Larsen et al. ). However, in the latter studies, 13 C offsets among multiple eAAs between consumers and their food resources varied among different consumer–resource relationships, indicating that there is a need for controlled feeding experiments on a wider range of taxa, specifically testing persistence of eAA fingerprints from dietary protein into consumer tissue (Whiteman et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our understanding of collembolan feeding habits at the species or functional group level is steadily increasing (Chamberlain et al, 2006;Ngosong et al, 2011;Ruess et al, 2007;Sechi et al, 2014a), but several gaps still exist. It is known that Collembola are closely associated with the rhizosphere food web being nutritionally supported by root-derived resources (Endlweber et al, 2009;Larsen et al, 2007;Sabais et al, 2012Larsen et al 2016b), but the path through which they obtain these resources is not yet clear. While euedaphic and hemiedaphic species have been shown to incorporate recent photosynthate carbon (C) from crops (Larsen et al, 2007;Ostle et al, 2007), A.M. recently demonstrated that only a fraction of these plant derived resources derives from direct foraging on roots.…”
Section: Introductionmentioning
confidence: 99%